Reparametrization of the COSMO Solvent Model for Semiempirical Methods PM6 and PM7 - Kříž, Kristian; Řezáč, Jan (Journal of chemical information and modeling, 2019)
An accurate description of solvation effects is of high importance in modeling biomolecular systems. Our main interest is to find an accurate yet efficient solvation model for semiempirical quantum-mechanical methods applicable to large protein-ligand complexes in the context of computer-aided drug design. We present a survey of readily available methods and a new reparametrization of the COSMO solvent model for PM6 and PM7 calculations in MOPAC. We have tested the reparametrized method on validation data sets of small drug-like molecules for which experimental solvation free energies are available as well as on a set of large model systems of the active site of carbonic anhydrase II interacting with a series of ligands for which experimental affinity values are known. In both cases, there is a significant improvement in accuracy after the reparametrization and the addition of a nonpolar term to the COSMO solvent model.
Keywords: termodynamika; karboanhydrasy; Thermodynamics; Carbonic Anhydrase Inhibitors; Ligands; Models, Molecular; Protein Conformation; molekulární modely; ligandy; Solvents; Quantum Theory; Carbonic Anhydrases; rozpouštědla; inhibitory karboanhydras; konformace proteinů; kvantová teorie